bdreshov S.N., Koibasova L.U., Abdullina Z.N., Atanbaeva G.K., Zhaparkulova N.I. Inﬂuence organic connections on contractive activity of lymph node: Institute of human and animal physiology SK MES RK, Almaty; 1. KAZSWPU, Almaty, 2; Al-Farabi Kazakh National University, Almaty (Eurasian Journal of Ecology, 2018)
This article shows that in influence organic connections rats there wasa decrease of the thoracic lymph duct. Influence of organic toxic substanceis studied on the contractive function of the isolated lymph nodes for rats.It is shown in experiments, that infringement in biochemical content ofa lymph and plasma of blood have been observed, represses contractiveactivity of lymph nodes. Lymph nodes are executed in an organism by numerous functions and most essential from them – it depositing, transport,barrier, exchange et al. In extreme situations lymph nodes can deposit aconsiderable volume внеклеточной at poisoning. The experiments showthat the long-term poisoning of rats by causes changes in biochemicalcomposition and physicochemical parameters of lymph and blood plasma. The was reduction in the lymph flow from the intestinal lymphaticvessel were observed. A decrease in the viscosity of the dry residue ofblood plasma and lymph after poisoning at rats organic toxic substanceswas recorded. There was a reliable decline of maintenance in total proteincontent of blood plasma and lymph. These data testify to reduction to theexchange function of the lymphatic system. Under the poisoning by substances there were observed the violation of the rheological properties ofblood and lymph, the increase in viscosity, and accelerated clotting whichdeteriorated the fluidity of both blood and lymph.Key words: lymph, lymph dynamics, lymph nodes, contractile activity